A new virtue-centred education for democratic citizenship. Issue 2 (1st September 2018) - Yu, Tianlong
Guided by a commitment to democratic citizenship needed in Chinese society, this paper makes the case for a new virtue-centred education. Specifically, the paper argues that to revamp and reclaim virtue-centred education: virtues should be emphasized for citizenship building over other purposes; virtues for citizenship must be social justice oriented; and virtues for democratic citizenship and social justice should be political and intellectual in nature, and need to be actively cultivated in schools.